Middle Pleistocene environments, landscapes and tephrostratigraphy of the Armenian Highlands: evidence from Bird Farm 1, Hrazdan Valley. (13th September 2021) - Sherriff, Jenni E.; Wilkinson, Keith N.; Harding, Poppy; Hawkins, Hayley; Timms, Rhys G. O.; Adler, Daniel S.; Beverly, Emily J.; Blockley, Simon P. E.; Gasparyan, Boris; Manning, Christina J.; Mark, Darren; Nahapetyan, Samvel; et al.
ABSTRACT: The significance of the southern Caucasus in understanding Pleistocene hominin expansions is well established. However, the palaeoenvironments in which Palaeolithic occupation of the region took place are presently poorly defined. The Hrazdan river valley, Armenian Highlands, contains a rich Palaeolithic record alongside Middle Pleistocene volcanic, fluvial and lacustrine strata, and thus offer exciting potential for palaeoenvironmental reconstruction. We present the first results of sedimentological, geochemical, tephrostratigraphical and biological (diatoms) study of the sequence of Bird Farm 1, located in the central part of the valley. These data show six phases of landscape development during the interval 440–200 ka. The sequence represents the first quantitative Pleistocene diatom record from the Armenian Highlands and the southern Caucasus, and indicates the persistence of a deep, stratified lacustrine system, with evidence for changing lake productivity that is tentatively linked to climate. Furthermore, major element chemical characterization of visible and crypto‐tephra horizons in the sequence enables the first stages of the development of a regional tephrostratigraphy. Together, the evidence from Bird Farm 1 demonstrates the importance of lacustrine archives in the region for palaeoenvironmental reconstruction and highlights the potential for linkages between archives on both a local and regional scale.